The Efficacyofantiscabies Medicinetohealing Scabiesin Patient Who Received Personal Hygiene Education - Feny Tunjungsari; Didik Tamtomo; Bhisma Murti; Yusrin Aulia (Saintika Medika, 2019)
The prevalence of the scabies disease in a populated area (e.g islamic boarding schools)is still high .It is possible that disease skabies are still found here because the higiene individuals from the community .Skabies disease is easily treated , but to progress , the disease remains a big problem in the specific community health .This study attempts to analyze the effectiveness of an anti skabies permethrine comparedgameksanto healing patients whohas been getting an  individuals higiene educationSamples were 40 student the Islamic boarding in the malang district the age range of 12 - 18 years taken by random. The dependent variable was cure from scabies. The independent variable included anti-scabies (Gamexan and Permethrine). The sample taken as random.Research will be tested using chi-square to analized the data.The experimental work on chi square statistically from the analysis does not obtain a significant relation ( p = 1,000 ) between the provision of treatment antiscabies gameksan and permethrine with healing on the subjects of research get education higiene individuals.Although statistically no meaning, but can be concluded that clinically better to use gameksan and permethrine, if the subject of study get education nice about education higiene individuals, there is no different effect between the provision of gameksan with permethrine.